Membaca Poststrukturalisme pada Karya Sastra - Budianto, V. Irmayanti Meliono (UI Scholars Hub, 2007)
Poststructuralism can be employed as a method to analyse literary work. As text that contains literary expression of human life, literary work is open to interpretation and critical analysis. Poststructural approach deconstructs and reconstructs the conceptual construct of writing, metalanguage, and subjectivity in a text.